INFLUENCE OF Trichoderma viride ON MYCOECRISOTROPH PATOGENES OF THE ROOT SYSTEM OF POTATOES (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
It is established the perspective of wide application T. viride for protection of plants from root inhabitant patogenes and utilization accumulating in soil foreign polymeric compound, used for protection against the pests of agricultural cultures.